Estado nutricional pré-gestacional, ganho de peso gestacional e peso ao nascer na coorte de nascimento BRISA: uma abordagem com modelagem de equações estruturais - Lima, Raina Jansen Cutrim Propp (2016)
Objective. This study aims to analyze the effects of prepregnancy nutritional status and gestational weight gain on birth weight. Methodology. Cross-sectional study involving 5,024 mothers and their newborns who participated in the study BRISA São Luís - MA. Data were collected in 2010 and were applied two questionnaires after delivery: one with maternal data and other newborn´s data. The main explanatory variables were prepregnancy BMI and gestational weight gain. Theoretical model was proposed to explain the total, direct and indirect effects, using structural equation modeling in the analysis, with adjustment for sociodemographic variables, life habits and maternal comorbidities, with the outcome birth weight. Results. The final model had good fit according to indicators RMSEA, CFI / TLI and WRMR. The prepregnancy BMI had total effect (Standardized Coefficient SC=0.126; p <0.001) and direct (SC=0.211; p <0.001) positive on the newborn's weight, plus negative indirect effect on the total gestational weight gain. Gestational weight gain in turn had the highest effect on birth weight (SC=0.280; p <0.001), including modifying the effect of other variables. Socioeconomic status, maternal age, more stable marital status and gestational diabetes had positive total effects, while high blood pressure and smoking during pregnancy had negative effects on birth weight. Alcohol use during pregnancy showed no total effect. Conclusion. Mothers with higher prepregnancy BMI can have children with higher weight, as well as those with high gestational weight gain. These associations highlight the need for greater attention to the health of women of reproductive age and maintaining proper weight gain during pregnancy, which could contribute to reducing risks of maternal complications and newborn.